Evaluation and Refractive Results Comparison of MIOL-SOFT-2-13 IOL Implantation with Foreign Models - D. F. Belov; V. P. Nikolaenko; V. V. Kovaleva (Oftalʹmologiâ)
Purpose. Evaluation and refractive results comparison of MIOL-SOFT-2-13 (ReperNN, Russia) IOL implantation with foreign models. Material and methods. The study included 816 patients (816 eyes) who underwent phacoemulsification (PE) with IOL implantation, divided into four groups depending on IOL model: MIOL-SOFT-2-13 (Reper-NN, Russia) (n = 199); SA60AT (Alcon, USA) (n = 237); Adapt AO (Bausch&Lomb, USA) (n = 179); Acryfold 601 (Appasamy Associates, India) (n = 201). All patients underwent optical biometry using IOL-Master 500 (Carl Zeiss, Germany). A month after PE spherical equivalent of refraction was assessed by Topcon8800 (Japan). Mean calculation error (ME) and mean absolute error (MAE) were used as a IOL calculation accuracy criterion. Results. Zeroing of ME allowed to determine real aconstant of MIOL-SOFT-2-13 (119.83 instead of 118.4 declared by the manufacturer). MAE in the groups was: 0.39 ± 0.27, 0.33 ± 0.35, 0.38 ± 0.31 and 0.38 ± 0.30 D, respectively (p = 0.068). All IOLs demonstrated hitting the target refraction within ±1.00 D in more than 95 % of cases. Conclusion. MIOL-SOFT-2-13 has comparable refractive results with other monofocal IOLs used in national medical insurance system. MIOL-SOFT-2-13 achieves target refraction within ±1.00 D in 98 % of cases.To obtain optimal refractive results, an optimized aconstant of 118.83 is required.